2004
DOI: 10.1002/jcp.20121
|View full text |Cite
|
Sign up to set email alerts
|

Expression and localization of Muc4/sialomucin complex (SMC) in the adult and developing rat intestine: Implications for Muc4/SMC function

Abstract: Muc4/sialomucin complex (SMC) is a high molecular mass heterodimeric membrane mucin, encoded by a single gene, and originally discovered in a highly metastatic ascites rat mammary adenocarcinoma. Subsequent studies have shown that it is a prominent component of many accessible and vulnerable epithelia, including the gastrointestinal tract. Immunoblot and immunofluorescence analyses demonstrated that Muc4/SMC expression in the rat small intestine increases from proximal to distal regions and is located predomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
3
10
0
Order By: Relevance
“…Clearly the spatio-temporal pattern of expression of Muc4 is organ-and cell-specific. These results are in agreement with previous data in human (12) and rat (48) and confirm the dual role of MUC4, especially in the intestine, as a membrane-associated protein before cytodifferentiation and both as a membraneassociated and secreted protein (localization in secretory granules of goblet cells) after cytodifferentiation. Altogether these studies indicate that MUC4 has a spatio-temporal pattern of expression both in developing human and rodents, which corrobates its important role in cytodifferentiation in both species.…”
Section: Discussionsupporting
confidence: 93%
“…Clearly the spatio-temporal pattern of expression of Muc4 is organ-and cell-specific. These results are in agreement with previous data in human (12) and rat (48) and confirm the dual role of MUC4, especially in the intestine, as a membrane-associated protein before cytodifferentiation and both as a membraneassociated and secreted protein (localization in secretory granules of goblet cells) after cytodifferentiation. Altogether these studies indicate that MUC4 has a spatio-temporal pattern of expression both in developing human and rodents, which corrobates its important role in cytodifferentiation in both species.…”
Section: Discussionsupporting
confidence: 93%
“…They are anchored to the apical cell surface of epithelial cells and are a major component of the glycocalyx. In the intestine, MUC4 is one of such prominent transmembrane-associated mucins [31]. In the present study, we showed that proteolysis of caseins by lactic bacteria (L. delbrueckii ssp.…”
Section: Discussionsupporting
confidence: 53%
“…This mucin has its three typical domains next to the large PTS domain at the extracellular cell surface. MUC4 is just as the SEA mucins cleaved during biosynthesis [18]. Most transmembrane mucins are found in the gastrointestinal tract, MUC1, MUC3, MUC4, MUC12, MUC13, MUC16, and MUC17.…”
Section: Mucinsmentioning
confidence: 99%